NATURAL RESOURCES OF MEDICINAL PLANTS AND THEIR RATIONAL USE IN THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
Recently, the problem of protection and rational use of the gene pool, includingendemic and rare medicinal plants, remains a problem. The expansion of exploitation of plantresources has caused certain plant communities and their components to undergo changes, andsome plant species are close to extinction. Changes in the habitat conditions of endemic andrare species under the influence of anthropogenic factors can lead to a reduction in the range. Topreserve plant species whose state in nature is of serious concern, as well as for the rational use ofplant resources, it is necessary to take into account all plant species that need protection.
Keywords: medicinal plant raw materials, reserves of raw materials, habitats, resources, ecology, endemic plants.